Statistics for management and economics : a systematic approach - Keller, Gerald; Warrack, Brian ;Bartel, Henry (Belmont, California : Wadsworth Publishing Company, 1988)
Statistics is a required course in various programs of study, including business and economics, in almost all universities. While the material covered, the level of difficulty, and the approach vary enormously, most have one aspect in common: the course is typically the most unpopular in the academic program.
Chapter 1. What Is Statistics? -- Part One. Descriptive Measures and Probability -- Chapter 2. Descriptive Statistics -- Chapter 3. Probability -- Chapter 4. Probability Distributions -- Part Two. Statistical Sciences --Chapter 5. Statistical Inference: Introduction -- Chapter 6. Sampling and Sampling Distributions -- Chapter 7. Inference About the Description of a Single Population :Interval Scale -- Chapter 8. Inference About the Description of a Single Population: Nominal Scale -- Chapter 9. Inference About the Comparison of Two Populations: Interval Scale -- Chapter 10. Inference About the Comparison of Two Populations: Nominal Scale -- Chapter 11. Statistical Inference: A Review of Chapters 7 Through 10 -- Chapter 12. Analysis of Variance -- Chapter 13. Chi-Square Tests -- Chapter 14. Nonparametric Statistics -- Chapter 15. Simple Linear Regression and Correlation -- Chapter 16. Multiple Regression -- Chapter 17. Multiple Regression Models -- Chapter 18. Statistical Inference: Conclusion -- Part Three. Applications -- Chapter 19. Time Series and Forecasting -- Chapter 20. Index Numbers -- Chapter 21. Decision Analysis.
Includes index.
Keywords: ECONOMIC -- STATISTICAL METHOD